Dkk-3 Induces Apoptosis Through Mitochondrial and Fas Death Receptor Pathways in Human Mucinous Ovarian Cancer Cells. Issue 3 (1st March 2015) - Takata, Aiko; Terauchi, Masakazu; Hiramitsu, Shiro; Uno, Masaya; Wakana, Kimio; Kubota, Toshiro
Abstract : Objective: Dkk-3 is a Wnt signaling inhibitor that is frequently inactivated in human cancers. Dkk-3 possesses an antiproliferative activity and induces apoptosis in tumor cells, suggesting that it functions as a tumor suppressor. In this study, we investigated the molecular function of Dkk-3 in human ovarian cancer cells. Methods: We assessed the levels of Dkk-3 protein expression in human mucinous and clear cell ovarian cancer cells, and compared cell viabilities between cell lines that expressed Dkk-3 and those that did not, as well as between cells that expressed Dkk-3 and those whose expression of Dkk-3 was reduced by small interfering RNA. We also evaluated the characteristic fragmentation of DNA to detect apoptosis in Dkk-3–deficient cells. To further investigate the molecular mechanisms of apoptosis, we assessed the expression of molecules involved in apoptosis signaling pathways in Dkk-3–deficient cells. Results: The expression of the Dkk-3 protein was observed in most of the ovarian cancer cell lines tested. Dkk-3–deficient cells showed faster growth than Dkk-3–replete cells. The characteristic fragmentation of DNA was not observed in Dkk-3–deficient cells, which showed decreased levels of expression in caspase-3, activated caspase-9, Bax, p53, activated caspase-8, and Fas/CD95, as well as an increase in Bcl-2 expression. Conclusions: Although Dkk-3 expression was observed in most of human ovarian cancer cell lines, Dkk-3 has a tumor-suppressive function and a proapoptotic effect, inducing apoptosis through mitochondrial and Fas death receptor pathways in human mucinous ovarian cancer MCAS cells.